PENGAWASAN DAN EVALUASI PROGRAM BAHASA ARAB DI PONDOK PESANTREN - Bako, Fitri Mawaddah; Masrurah, Faiqatul; Tuli, Friske; Arifah, Desiy (Arabi : Journal of Arabic Studies, 2018)
This study identified how the supervision and evaluation of the Arabic program in the girl pesantren Hafsah Binti Umar Malang Batu. Data were collected through observation and interview. The subject of his research was two Arabic teachers at the pesantren. To get the data, the researcher conducted observation and interview directly to the Arabic teacher in the Pesantren where the researcher participated in observing the activit. Finally, this study concluded that the supervision of the Arabic language program at the girl pesantren Hafsah Binti Umar has not been fully done by the teachers since some of the programs that have been designed have not been written in the structure of the Pesantren Hafsah Binti Umar program. For the evaluation of the Arabic program, the chairman of the pesantren evaluated by asking each program that has been implemented to each teacher in their respective fields at the end of each semester.